ANALISIS GAYA KEPEMIMPINAN DAN KINERJA TERHADAP KEPUASAN KERJA DINAS PERINDUSTRIAN DAN PERDAGANGAN (DISPERINDAG) PROVINSI KALIMANTAN BARAT - NUGRAHA B11108127, GUSTI JEFFY (Jurnal Manajemen Update, 2015)
One of competitive advantages of an organizational is a good job performance of theemployees. Leadership styles and job satisfaction constitute factors considered are able toincrease employees’ job performance. This study was a case study to analyze the influence ofleadership styles and job performance towards employees’ job performance at Department ofIndustry and Trade in Pontianak, West Kalimantan province.  The method employed in thisstudy was survey and explanatory research, with 142 populations of employees weresurveyed. Two hypotheses namely, relationship between leadership styles and jobperformance and relationship between job satisfaction and job performance used in thisstudy. Result finding indicated that leadership styles and job satisfaction did not significantlyaffect influenced job performance of the employees.Keywords : Leadership styles, Job satisfaction, Job performance, Survey and Explanatoryresearch